Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12931-023-02406-5
|View full text |Cite
|
Sign up to set email alerts
|

IRAK-M has effects in regulation of lung epithelial inflammation

Abstract: Background Epithelial barrier is important for asthma development by shaping immune responses. Airway expressing-IL-1 receptor-associated kinase (IRAK)-M of Toll-like receptor pathway was involved in immunoregulation of airway inflammation through influencing activities of macrophages and dendritic cells or T cell differentiation. Whether IRAK-M has effect on cellular immunity in airway epithelial cells upon stimulation remains unclear. Methods We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…As the A20 protein, IRAK-M is involved in immunoregulation of airway inflammation. Although the role of IRAK-M in the respiratory tract immune responses was demonstrated by its influence on macrophages, dendritic cells, and T cells, recent studies highlighted its role in RECs ( 46 ). It was demonstrated that the knockdown of IRAK-M in EAS-2B and A549 cells significantly increased their ability to produce IL-6, IL-8, CXCL10, and CXCL11 in response to IL-1β, TNF-α, or IL-33 stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…As the A20 protein, IRAK-M is involved in immunoregulation of airway inflammation. Although the role of IRAK-M in the respiratory tract immune responses was demonstrated by its influence on macrophages, dendritic cells, and T cells, recent studies highlighted its role in RECs ( 46 ). It was demonstrated that the knockdown of IRAK-M in EAS-2B and A549 cells significantly increased their ability to produce IL-6, IL-8, CXCL10, and CXCL11 in response to IL-1β, TNF-α, or IL-33 stimulation.…”
Section: Discussionmentioning
confidence: 99%